Asupan gizi dan status gizi sebagai faktor risiko hipertensi esensial pada lansia di Puskesmas Curup dan Perumnas Kabupaten Rejang Lebong Propinsi Bengkulu - Agung Riyadi; P Wiyono; R Dwi Budiningsari (Jurnal Gizi Klinik Indonesia, 2007)
Background: Hypertension is happened generally at someone who has age more than 40 year. The prevalence of hypertension was tend to increase along with the increasing of amount of the elderly. Changing of nutrition status and unfavorable nutrition intakes like is high fat, sodium and low micronutrients (potassium, calcium, magnesium) have an effect to incidence of essential hypertension. Retreating of biologic accompanying aging process sometimes make the elderly become resistance to get quality of intakes nutrition.Objective: The study was conducted to know relations between nutrition intakes and nutrition status with occurrence on essential hypertension of the elderly in the health center Curup and Perumnas, Rejang Lebong District.Method: The study was observational analytic with case control matched study. Subject of the study was divided into two group i.e. case and control with comparison case and control 1:1 which matched to age and sex. Total subject were 150, taken by simple random method. The cases were essential hypertension patients who had recently diagnosed by doctors. Blood pressure measurements were three times in supine position. Hypertension was defined as average of three times supine systolic/diastolic blood pressures at p >140/ 90 mmHg. Nutrition status was determined by Body Mass Index (BMI). Intake nutrients were collected using Food Frequency Questionnaire (FFQ) in the last 3 months by using food model. χ 2 McNemar were used to bivariate analytic and condition logistic regression to identify risk factors associated with essential hypertension.Result: This study showed that there were 4 variables significantly related with essential hypertension, i.e. intakes of sodium (OR: 3.43; CI 95%:1.09-10.77), potassium (OR: 0.24; CI 95%:0.07-0.84), stress (OR: 3.79; CI 95%:1.18-12.12), and obesity (OR: 4.57; CI 95%:1.49-13.95). The no significant correlation (p>0.05) identified for intakes of fat, calcium, magnesium, coffee consumption, smoking status and family history of essential hypertension.Conclusion: High intake of sodium, stress and obesity were the risk factors on occurrence of essential hypertension. In the other hand, high intake of potassium were reduce the risk on occurrence of essential hypertension (protective factor) in the health center Curup and Perumnas, Rejang Lebong District.